Cadmium content and physicochemical characterization of cocoa beans and cocoa paste (Theobroma cacao). - Revilla Escobar, Karol; Intriago Flor , Frank; Chávez García , gema; Vásquez Cortez, Luis; Alvarado Vásquez , Kerly; Vera Chang, Jaime; Radice , Matteo; Maddela Naga, Raju (Innovaciencia, 2023)
Introduction: heavy metals such as cadmium (Cd) are a worldwide concern; recent research has concluded that they are related to health risks caused by the ingestion of contaminated food. Objective: the objective of this research was to evaluate the cadmium content and physicochemical characteristics in almonds and cocoa paste. Materials and Methods: a Completely Randomized Design (CRD) with three replications was used to determine the significant difference between the mean of the treatments using the Duncan post hoc statistical test (p
Keywords: almendras de cacao, beneficiado, cromatografía, cadmio